Modular depressant constructed via MA-linker assembly: Dual functionality in selective inhibition and aggregation of serpentine during the flotation of pyrite - Heng Zhang; Zhi Lei; Hao Tang; Hao-Ran Wu; Xu-Gang Zhang; Peng-Fei Xu (Minerals Engineering, 2026)

Insights into EPS-mediated simultaneous dewatering and stabilization of landfilled tannery sludge via combined chemical conditioning and PVD-vacuum preloading - Yang Xu; Fei Jin; Xiaowen Liu; Weixin Cheng; Ran Yu; Jia-Lei Wan; Jia-Hao Xie; Yan-Jun Du (Chemical Engineering Journal, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

A self-perpetuating cycle: how heavy metals shape DOM chemistry to promote their own immobilization in soil - Shuyi Zhang; Wenjun Zhang; Ye Li; Longfei Zhao; Chunmei Ran; Hongming Cai; Zhineng Hao; Junjie Zhang; Lei Wang (Environmental Monitoring and Assessment, 2026)

Multiple magmatic episodes and metamorphic overprinting in the Archean Anshan Complex: Integrated zircon–rutile–titanite–apatite U–Pb geochronology and trace-element constraints - Qing-Feng Mei; Jin-Hui Yang; Jin-Feng Sun; Lei Xu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu; Hao Wang (Lithos, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Pulsed ultrasound-assisted deep eutectic solvent-mediated stabilization and bioactivity enhancement of hydrolysable tannins from chestnut (Castanea mollissima) burrs - Xingying Xue; Zhiwen Qi; Hao Zhou; Ran Tao; Wenjun Li; Qin He; Jiandu Lei; Chengzhang Wang (Food Research International, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Rock failure mechanism and stability control of extraction roadways under extreme non-uniform pressure - Lei Fan; Ju-cai Chang; Hao-ran Chen (Applied Geophysics, 2026)

Comprehensive review on the impact of building envelopes on indoor thermal comfort in office buildings: Balancing occupant comfort and energy efficiency - Duqin Hong; Ran Cheng; Hao Lei; Xiaohui Zhou; Liu Yang; Chi Feng; Shan Gao (Building and Environment, 2026)

An optimal method for GNSS water vapor tomography based on parameter adaptation - Fei Yang; Ruixian Hao; Haoyu Wang; Lei Wang; Zhicai Li; Junxi Zheng; Yingying Wang; Ran Chen (GPS Solutions, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

The coexistence of Bacillus haynesii and Bacillus tequilensis achieves synchronous algicidal activity and denitrification and enhances the MC-LR degradation of phycosphere microbiota - Yuzi Xing; Lei Zheng; Zixuan Li; Guizhen Hao; Xue Wang; Ran Tao; Qi Tian; Yaoxin Zhang; Haozhe Zhang (Journal of Hazardous Materials, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Apatite geochemical indicators for magma mixing and fractional crystallization in the origin of A-type granite - Bao-Quan Zhou; Jin-Hui Yang; Jin-Feng Sun; Hao Wang; Yu-Sheng Zhu; Ya-Dong Wu; Qing-Feng Mei; Lei Xu; Jing Ran (Lithos, 2025)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Comparative transcriptomic insights into key genes for biomass production and lipid synthesis in Chlorella sorokiniana mutated by argon and air atmospheric and room temperature plasma at different culture stages: Common mechanisms and unique differences - Hongwei Li; Xin Sun; Wei Li; Lei Ye; Xiaoxiao Sun; Ran Hao; Xiaoli Guo (Journal of Cleaner Production, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Promotion strategy of low-carbon multimodal transportation considering government regulation and cargo owners’ willingness - Xinghua Hu; Ruizi Cheng; Jiahao Zhao; Ran Wang; Tingting Zhang; Hao Lei; Ba Liu (Environment, Development and Sustainability, 2024)

A two-stage approach to siting electric bus charging stations considering future-current demand - Xinghua Hu; Hao Lei; Dongde Deng; Yuhang Bi; Jiahao Zhao; Ran Wang (Journal of Cleaner Production, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Potential effects of Ag ion on the host by changing the structure of its gut microbiota - Xin-Lei Wang; Nanyang Yu; Ying-Xue Ma; Hao-Ran Zhou; Chuan Wang; Si Wei; Ai-Jun Miao (Journal of Hazardous Materials, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Numerical simulation of dynamic responses of semi-rigid rockfall protection barriers subjected to impact loading at different positions - Xin Qi; Lei Zhao; Chao-Ran Hao; Zhi-Xiang Yu; Shi-Chun Zhao (Bulletin of Engineering Geology and the Environment, 2022)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)